Final design of the cryostat for the high luminosity LHC magnets. Issue 1 (1st May 2022) - Ramos, D; Vande Craen, A; Prin, H; Leclercq, Y; Williams, L; Struik, M; Barlow, G; Riu Martinez, O; Wong Luis, B; Parma, V; Savary, F; Todesco, E
Abstract: The high luminosity LHC project (HL-LHC) aims at increasing proton collisions by a factor of ten whilst extending physics exploitation until 2035. Its performance will rely on new focusing quadrupoles, beam separation dipoles and corrector magnets with large apertures to be installed on both sides of the ATLAS and CMS experiments. A dedicated cryostat design of about 1 m in diameter was developed for operation of these magnets at 1.9 K, comprising the required cryogenic circuits, interconnects, supports, insulation, and instrumentation systems. Six cryostats with various lengths in the range of 8 to 11 m are required on each side of the interaction points to house the triplet magnets, correctors and the first separation dipole. These cryostats will be linked through flexible interconnects to form a continuous vacuum insulation and cryogenic system of about 60 m in length. The second rearmost separation dipole requires a stand-alone cryostat of 15 m in length but nevertheless features common design principles. We present the design of these cryostats, from a conceptual stage towards the final design. Assembly aspects are also addressed, including a modular approach affording flexibility and simplification of the manufacturing and assembly processes.